2014
DOI: 10.1186/gb-2014-15-4-r63
|View full text |Cite
|
Sign up to set email alerts
|

Cross-enhancement of ANGPTL4 transcription by HIF1 alpha and PPAR beta/delta is the result of the conformational proximity of two response elements

Abstract: BackgroundSynergistic transcriptional activation by different stimuli has been reported along with a diverse array of mechanisms, but the full scope of these mechanisms has yet to be elucidated.ResultsWe present a detailed investigation of hypoxia-inducible factor (HIF) 1 dependent gene expression in endothelial cells which suggests the importance of crosstalk between the peroxisome proliferator-activated receptor (PPAR) β/δ and HIF signaling axes. A migration assay shows a synergistic interaction between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 61 publications
(82 reference statements)
3
65
2
Order By: Relevance
“…Angptl4 is a potent anti-angiogenic and anti-inflammatory factor, which is under the transcriptional control of PPARγ (50). FABP4 and CD36 are also PPARγ target genes involved in lipid metabolism, and PPARγ activation was found to induce FABP4 mRNA in human monocytes (51).…”
Section: Discussionmentioning
confidence: 99%
“…Angptl4 is a potent anti-angiogenic and anti-inflammatory factor, which is under the transcriptional control of PPARγ (50). FABP4 and CD36 are also PPARγ target genes involved in lipid metabolism, and PPARγ activation was found to induce FABP4 mRNA in human monocytes (51).…”
Section: Discussionmentioning
confidence: 99%
“…Gene-set differential expression analysis of patient samples at TKI resistance compared with pre-TKI samples showed alterations in hypoxia-related pathways and upregulation of hypoxia response genes such as ANGPTL4 (ref. 20 and Supplemental Table 5). We also found a hypoxia-responsive element (HRE) in the BMX promoter (Figure 3B), and a luciferase reporter assay showed HRE-dependent promoter activity under hypoxic conditions ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Megabase TADs are reportedly already formed in ES cells and largely conserved through development, among different cell types and in response to specific stimuli (Dixon et al , ; Jin et al , ), although recent studies have suggested that submegabase (sub)‐TADs could have plastic properties (Phillips‐Cremins et al , ; Siersbaek et al , ; Kim et al , ; Ogiyama et al , ). Furthermore, using 3C, circular 3C (4C), and ChIA‐PET, we showed that human ECs have cell type‐specific small chromatin loops, which correlate with gene expression profiles (Kanki et al , ; Mimura et al , ; Papantonis et al , ; Inoue et al , ). However, there is no clear consensus on the plasticity of chromatin interactions ( i.e ., chromatin loops or small TADs) in response to external stimuli, particularly in terminally differentiated cells.…”
Section: Introductionmentioning
confidence: 99%